Living with moral disagreement - Crisp, R (Springer Verlag, 2020)
This paper argues that suspension of judgement is the appropriate response to disagreement about ultimate moral principles, and outlines the implications of such a response. It begins with an argument influenced by Sextus and Sidgwick for the rationality of suspension, and then illustrates fundamental disagreement with the case of promising. Replies are offered to the arguments against the rationality of suspension offered by Robert Audi in his discussion of moral perception. It is noted in particular that such rationality does not depend on the assumption that epistemic peerhood is widespread. The limited nature of ethical agreement is illustrated, along with the limited implications of disagreement if a less adversarial and more constructive ethical methodology is adopted.